Immunological properties of protein hormones : proceedings of Meeting organized under the auspices of Accademia Nazionale dei Lincei and of Consiglio Nazionale delle Ricerche, Rome, June 1964 - Polvani, Filippo; Crosignani, P. G. (Pier Giorgio) (Academic Press, 1966)
Immunological Properties of Protein Hormones.